2018
DOI: 10.4103/ija.ija_717_17
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of transnasal humidified rapid-insufflation ventilatory exchange versus traditional preoxygenation followed by apnoeic oxygenation in delaying desaturation during apnoea: A preliminary study

Abstract: Background and Aims:Transnasal humidified rapid-insufflation ventilatory exchange (THRIVE) during apnoea has shown to delay desaturation. The primary objective was to compare time to desaturate to <90% during apnoea with THRIVE versus traditional preoxygenation followed by apnoeic oxygenation.Methods:This prospective, randomised, single-blinded study was conducted in 10 adult patients presenting for direct laryngoscopy under general anaesthesia without endotracheal intubation. Group P patients were preoxygenat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 15 publications
(19 reference statements)
0
30
0
Order By: Relevance
“…The results of previous studies have been mixed in respect of physiological endpoints of this type [14][15][16][17][18][19][20][21][22][23][24]26]. This probably reflects differences in patient groups, in the technicalities of how HFNO was administered and in how the data were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of previous studies have been mixed in respect of physiological endpoints of this type [14][15][16][17][18][19][20][21][22][23][24]26]. This probably reflects differences in patient groups, in the technicalities of how HFNO was administered and in how the data were obtained.…”
Section: Discussionmentioning
confidence: 99%
“…Studies of pre-oxygenation with HFNO have had mixed results [13][14][15][16][17][18][19][20][21][22][23]. Technicalities matter: in particular, a closed mouth appears to be important when pre-oxygenating a patient with HFNO [15,17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 8 Furthermore, studies have indicated that HFNO results in the accumulation CO 2 because of insufficient ventilation. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%
“…High-flow nasal cannula (HFNC) provides high-flow (8-80 l/min) inhalation gas with adjustable and relatively constant oxygen concentration (21%~100%), temperature (31-37℃) and humidity (5,6). Compared with conventional oxygenation methods, the advantage of HFNC is that the continuous positive airway pressure (CPAP) can cause mild lung recruitment (7,8), thus, it can reduce the ventilation dead space to improve the oxygenation of critically ill patients and improve patient comfort (9)(10)(11). In addition, some features of HFNC, such as increasing FRC and endexpiratory lung volume (EELV), can improve the oxygenation status of obese patients (12,13).…”
mentioning
confidence: 99%